Stability, security, democracy: explaining shifts in the narrative of the European Neighbourhood Policy. Issue 1 (2nd January 2017) - Cianciara, Agnieszka K.
Abstract: Stability, security and democracy are typically perceived as objectives of the European Neighbourhood Policy (ENP). As a result, scholars usually reflect on their rival or complementary character, debating EU pursuit of interests (stability and security) or values (democracy). This article argues that objectives should also be seen as components of a narrative, which is a product of strategic agency of EU institutions seeking internal legitimacy. While examining key ENP strategy documents, the article identifies two major shifts in the ENP narrative. Whereas literature usually focuses on how narratives are reproduced and sustained when confronted with contestation, this article seeks to explain why actors opt for narrative reconstruction instead of narrative reproduction. The argument stipulates that narrative shifts are related to actors' legitimacy concerns enhanced by uncertainty and insecurity resulting from internal and external crises.